Investigating transformation kinetics of yttrium hydroxide to yttrium oxide - Priya R.; Kainth S.; Kumar D.; Sharma P.; Diwan P.K.; Pandey O.P. (My University, 2025)
The transformation kinetics involved during the formation of yttrium oxide through thermal dehydration of yttrium hydroxide was studied through differential thermal analysis (DTA) at multiple heating rates (1, 5, 7, 10 °C/min) in air. The yttrium hydroxide dehydrates in two steps to form yttrium oxide. The intermediate compound, i.e., YOOH was formed at 350 °C. The phase formation was confirmed through XRD and Le-Bail profile matching. FESEM confirms the dehydration of yttrium hydroxide and a rod-shaped microstructure was observed. An increase in temperature resulted in shrinkage of the rods. The kinetic triplets (activation energy, pre-exponential factor and reaction mechanism) were estimated for both the steps. The Straink method was used to evaluate activation energy, whereas the reaction mechanism was identified through the integral master plot method. The activation energy was 219.6 kJ/mol and 431.3 kJ/mol for step I and II of dehydration, respectively. Step I was dominated by the A2 reaction mechanism, while the F1 reaction mechanism was found in step II of yttrium hydroxide dehydration. © 2022 Elsevier B.V.